Dasar-Dasar Pendidikan dalam Al-Qur'an - SINTA MASITHA; Mahyuddin Barni (CV. ITTC INDONESIA, 2025)
The foundation of education in the Qur’an emphasizes that the entire learning process must be based on tawhid guiding humans to recognize and serve Allah SWT. Education encompasses the integrated development of spiritual, intellectual, moral, and social aspects to produce knowledgeable individuals with noble character. Humans are regarded as the primary subjects of education, serving both as Allah’s servants and as stewards (khalifah) on earth. This study employs a library research method, an approach that examines various written sources such as the Qur’an, tafsir, scholarly books, journals, and other relevant academic works. The results indicate that education in the Qur’an is comprehensive, covering spiritual, intellectual, moral, social, and practical dimensions, all grounded in tawhid. Its purpose is to cultivate individuals who are faithful, virtuous, knowledgeable, and socially responsible as stewards of the earth. Beneficial knowledge, proper manners in seeking it, and a wise learning process are key to achieving holistic education.